AngioVac system guided removal of vegetations from pacemaker lead-related infective endocarditis. Issue 1 (20th January 2023) - Mahajan, Pranav; Aedma, Surya Kiran; Ally, Saeed; Garg, Anuj
Abstract : The AngioVac aspiration system is a catheter-based technique that has been used for removal of unwanted intravascular material in growing numbers of institutions around the world since 2013. It provides an alternative and a less invasive approach for the treatment of venous thromboembolism and intrinsic or cardiac implantable electronic devices (CIED)-related infective endocarditis. This system uses venous cannulas and extracorporeal filtering mechanisms to effectively remove thrombi or vegetations resulting in less invasion and minimal blood loss. We present a case of a woman in her mid-50s who underwent successful AngioVac-guided removal of lead vegetations followed by percutaneous CIED removal.